Effect of mixing ratio on the breakdown voltage of mineral and natural ester insulating oil blends - Sharin Ab Ghani; Imran Sutan Chairul; Mohd Shahril Ahmad Khiar; Nor Hidayah Rahim; Syahrun Nizam Md Arshad@Hashim (Bulletin of Electrical Engineering and Informatics, 2022)
To date, the most common insulating oil used in oil-immersed transformers is mineral insulating (MI) oil, which is derived from petroleum. Owing to the depletion of petroleum over the years, it can be anticipated that petroleum-derived products such as MI oils will also deplete in the future. MI oils are not only non-renewable, but they are also non-biodegradable, where these oils are harmful to the environment in cases of oil spillage. Therefore, the aim of this study is to investigate the potential of mixing MI oil with natural ester insulating (NEI) oil in order to reduce the high dependency on MI oil for transformer applications. The MI and NEI oils were mixed with different mixing ratios. AC breakdown voltage test was conducted on the MI-NEI oil blends according to the ASTM D1816 standard. From the results, it is found that the following mixing ratios (30% of MI oil + 70% of NEI oil, 20% of MI oil + 80% of NEI oil) result in significant improvement in terms of the AC breakdown voltage compared with unused MI oil. The flash point and corrosivity levels of the oil blends were also examined.